Adjuvant chemotherapy after surgery for pancreatic ductal adenocarcinoma: retrospective real-life data - Sophia Chikhladze; Ann-Kathrin Lederer; Lampros Kousoulas; Marilena Reinmuth; Olivia Sick; Stefan Fichtner-Feigl; Uwe A. Wittel (World Journal of Surgical Oncology, 2019)
Abstract Background The recommendation for postoperative chemotherapy in pancreatic ductal adenocarcinoma (PDAC) is based on prospective randomized trials. However, patients included in clinical trials do not often reflect the overall patient population treated in clinical practice. Materials and methods A retrospective review of all patients undergoing pancreas resection for PDAC between 2001 and 2013 was performed. Follow-up data from oncologists, general practitioners, or hospital patient files were available for 92% of patients. Results A total of 251 patients were included in our analysis. Chemotherapy was recommended for 223 patients, but 86 patients did not follow the recommendation. The application of the recommended chemotherapy, consisting of 6 cycles of gemcitabine, was only applied to 45 patients. Forty patients received the recommended number of cycles with dose reduction or prolonged intervals between cycles, and adjuvant chemotherapy was terminated prior to the intended completion of all 6 cycles in 54 patients. Survival of patients after adjuvant chemotherapy was increased compared to that of patients without chemotherapy (with recurrence 25.6 vs. 14.3 months, p = 0.001, and without recurrence 27.4 vs. 14.3 months, p <  0.001). Terminating chemotherapy prior to completion (p = 0.009) as well as a lower number of chemotherapy cycles (p = 0.026) was associated with a decreased survival. Conclusion Adjuvant chemotherapy improves overall and disease-free survival after curative pancreatic resection, but only a small fraction of patients completes the recommended 6 cycles of adjuvant chemotherapy. Our data indicates that performance status of patients after pancreas resections for PDAC requires not only highly biologically active but also well-tolerated adjuvant chemotherapy regimens.